Wearable sensors bring new benefits to continuous medical monitoring, real time physical activity assessment, baby monitoring and industrial applications. Issue 2 (16th March 2015) - Bloss, Richard
Abstract : Purpose: – The purpose of this paper is to review the recent advancements in the development of wearable sensors which can continuously monitor critical medical, assess athletic activity, watch babies and serve industrial applications. Design/methodology/approach: – The paper presents an in-depth review of a number of developments in wearable sensing and monitoring technologies for medical, athletic and industrial applications. Researchers and companies around the world were contacted to discuss their direction and progress in this field of medical condition and industrial monitoring, as well as discussions with medical personnel on the perceived benefits of such technology. Findings: – Dramatic progress is being made in continuous monitoring of many important body functions that indicate critical medical conditions that can be life-threatening, contribute to blindness or access activity. In the industrial arena, wearable devices bring remote monitoring to a new level. Practical implications: – Doctors will be able to replace one-off tests with continuous monitoring that provides a much better continuous real-time "view" into the patient's conditions. Wearable monitors will help provide much better medical care in the future. Industrial managers and others will be able to monitor and supervise remotely. Originality/value: – An expert insight into advancements in medical condition monitoring that replaces the one-time "finger prick" type testing only performed in the doctor's office. It is also a look at how wearable monitoring is greatly improved and serving athletics, the industry and parents.